Achieving High-Efficiency Error-Correcting Transmission of Qutrits with On-Chip Quantum Autoencoder - Wang, Denghui; Ma, Haoran; Chen, Donghui; Ye, Liao; Ruan, Fanjie; Wang, Yuehai; Yang, Jianyi (2025 Optical Fiber Communications Conference and Exhibition (OFC), 2025)
We designed a programmable quantum autoencoder on a silicon photonic chip with nearly no compression loss, which enabled us to propose and implement a new highly efficient error-correcting transmission protocol for qutrits.